2021
DOI: 10.1038/s41467-021-25646-9
|View full text |Cite
|
Sign up to set email alerts
|

The biogeographic differentiation of algal microbiomes in the upper ocean from pole to pole

Abstract: Eukaryotic phytoplankton are responsible for at least 20% of annual global carbon fixation. Their diversity and activity are shaped by interactions with prokaryotes as part of complex microbiomes. Although differences in their local species diversity have been estimated, we still have a limited understanding of environmental conditions responsible for compositional differences between local species communities on a large scale from pole to pole. Here, we show, based on pole-to-pole phytoplankton metatranscript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 93 publications
4
23
1
Order By: Relevance
“…30°. Similar results have been found earlier in terrestrial vertebrates when considering only the turnover component of β‐diversity (Castro‐Insua et al., 2016) and for the total β‐diversity of marine phytoplankton (Martin et al., 2021). It is noteworthy that our latitudinal patterns were related mainly to the replacement component for both taxonomic and functional decay (Appendix S4; Figure S4.7).…”
Section: Discussionsupporting
confidence: 89%
“…30°. Similar results have been found earlier in terrestrial vertebrates when considering only the turnover component of β‐diversity (Castro‐Insua et al., 2016) and for the total β‐diversity of marine phytoplankton (Martin et al., 2021). It is noteworthy that our latitudinal patterns were related mainly to the replacement component for both taxonomic and functional decay (Appendix S4; Figure S4.7).…”
Section: Discussionsupporting
confidence: 89%
“…A plausible explanation for such observation could be the sample origin or geography. Interestingly, a recent study [83] has provided evidence for biogeographic differentiation of algal microbiomes, showing ecological boundaries driven by differences in environmental conditions altering the spatial scaling of the algal microbiomes.…”
Section: Both Intrinsic and Extrinsic Factors Influence Microalgal-ba...mentioning
confidence: 99%
“…Due to the importance of marine microbiomes and the rapid development of molecular tools in the past decade, there have been increasing numbers of studies investigating environmental and ecophysiological factors selecting for a regional to global scale microbial diversity and richness. For example, several studies have revealed a decrease in both prokaryote and microeukaryote taxonomic diversity and richness with increasing latitude at the global scale (Fuhrman et al, 2008 ; Ibarbalz et al, 2019 ; Salazar et al, 2019 ; Martin et al, 2021 ). This observed pattern has been linked to the latitudinal relationship with temperature, suggesting that temperature is one of the most important environmental factors driving the species richness and taxonomic composition of upper ocean microbial communities.…”
Section: Introductionmentioning
confidence: 99%
“…This observed pattern has been linked to the latitudinal relationship with temperature, suggesting that temperature is one of the most important environmental factors driving the species richness and taxonomic composition of upper ocean microbial communities. Multiple studies have also illustrated biogeographical differentiation in the taxonomic and transcriptomic diversity of microbial communities between comparatively cold (polar) and warm (non-polar) waters, as well as unique algal microbiome co-occurrence networks and rates of net primary production (Behrenfeld et al, 2006 ; Ibarbalz et al, 2019 ; Salazar et al, 2019 ; Martin et al, 2021 ). Many of these differences are suggested to occur in the northern hemisphere around an annual-mean isotherm of 14–15°C as an ecological boundary or “breakpoint,” potentially selecting for thermal tolerance limits and affecting the kinetics of metabolism (Thomas et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%